SUSTAINABLE BENCHMARKS FOR TOURIST ACCOMMODATIONS IN BALI - Utami Dwipayanti, Ni Made (Bumi Lestari; Vol 6 No 1)
As part of our efforts to move towards sustainable development, it is very important to encourage the tourism industry to be more environmentally conscious because it consumes large amounts of resources. One way of achieving greater sensitivity is to identify benchmarks for energy and water use and for other aspects of hotel operations like the amount of solid waste generated. Benchmarks can be defined using data from existing hotels. The research project focused on tourist accommodation on Southern Part of Bali Island. It conducted a survey by mailed questionnaire of about 50% of the hotels on the island. The questionnaire obtained annual data on several sustainability criteria that are energy and water consumption, biodiversity conservation, resource conservation, cleaning chemical use, solid waste management and wastewater management. The data were used to derive baseline and best practice thresholds to improve the performance of tourist accommodation on Bali Island. The benchmarks, both baseline and best practice standards were developed mainly using the study results which established the average and the average of the top 25% of performers. The average of the top 10% of performers was also considered in selecting the best practice standard for indicators that required stricter standards. Within the benchmarking process, Green Globe 21 standards and some other studies were also being used for comparison purpose. In this survey, the difficulties were found in obtaining complete set of data from each respondents as well as gaining sufficient responses. Few hotels provided complete set of data. Data on energy and water consumption is the easiest to obtain, while data for other indicators only provided by less than 75% of respondents. Most of the survey results showed reasonable value compared to Green Globe 21 standards. Good performance of tourist accommodation in the survey was found in energy consumption indicator that the average and the average of the top 25% of performers were far stricter than the Green Globe 21 standards. The study concluded with benchmarks recommendation for each indicator that can be applied to tourist accommodations in Southern Part of Bali Island.
Keywords: tourist accommodation, sustainable performance, resources use, benchmark